1993
DOI: 10.1192/bjp.163.3.332
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin Rhythms in Seasonal Affective Disorder

Abstract: We examined 24-hour melatonin rhythms from 20 patients with seasonal affective disorder (SAD) and 20 healthy volunteers. Patients and controls were individually matched for age, sex, and month of study. Plasma samples were taken at hourly intervals, and were assayed for melatonin by radio-immunoassay. The 24-hourly melatonin estimations for each individual were fitted to a cosine curve, and the significance of the curve fits was calculated. Two analyses were performed. In analysis 1 the following were calculat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
2

Year Published

1997
1997
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(26 citation statements)
references
References 33 publications
0
24
0
2
Order By: Relevance
“…(Eastman et al, 1998; Lewy et al, 1998; Szeinberg et al, 2006; Terman et al, 1998; Wasdell et al, 2008). Research in diurnal animals confirms that morning and not evening light reverses depression like behavior induced by short photoperiod (Krivisky et al, 2012), However, there is also evidence against circadian phase changes as being a primary mechanism in SAD as well as a necessary and sufficient mediator of light treatment (Checkley et al, 1993; Eastman et al, 1993; Koorengevel et al., 2003; Murray et al, 2005; Rosenthal et al, 1990; Thompson et al, 1997). Previously, a large case control study conducted to investigate the relationship between DSPS and SAD (Lee et al, 2011) found that the proportion of SAD (syndromal and subsyndromal) is higher in patients with DSPS compared to controls.…”
Section: Discussionmentioning
confidence: 99%
“…(Eastman et al, 1998; Lewy et al, 1998; Szeinberg et al, 2006; Terman et al, 1998; Wasdell et al, 2008). Research in diurnal animals confirms that morning and not evening light reverses depression like behavior induced by short photoperiod (Krivisky et al, 2012), However, there is also evidence against circadian phase changes as being a primary mechanism in SAD as well as a necessary and sufficient mediator of light treatment (Checkley et al, 1993; Eastman et al, 1993; Koorengevel et al., 2003; Murray et al, 2005; Rosenthal et al, 1990; Thompson et al, 1997). Previously, a large case control study conducted to investigate the relationship between DSPS and SAD (Lee et al, 2011) found that the proportion of SAD (syndromal and subsyndromal) is higher in patients with DSPS compared to controls.…”
Section: Discussionmentioning
confidence: 99%
“…Studies done in areas of the world where there are less extreme seasonal differences may not find pronounced seasonal rhythms, particularly in individuals who are exposed to self-selected cycles of artificial light. Additional abnormalities in melatonin secretion in SAD patients, such as phase delays over twenty-four hours, have also been reported; however, other studies have reported no differences in circadian melatonin levels or rhythms in SAD patients (Checkley et al, 1993;Srinivasan et al, 2006). Therefore the link between abnormal or exaggerated melatonin rhythms and SAD is still up for debate.…”
Section: Seasonal Affective Disordermentioning
confidence: 99%
“…A number of studies provide evidence for abnormal melatonin levels in patients with SAD: high melatonin levels during daytime [101] , prolonged nocturnal melatonin secretion in winter [102] and a phase delay of melatonin release [103] . However, there are also studies which could not discriminate between patients and healthy controls on the basis of melatonin secretion patterns [104,105] . The phase shift hypothesis is nonetheless remarkable as many SAD patients are phase delayed in their chronobiological cycle.…”
Section: Pathophysiology Of Sad Chronobiological Hypothesismentioning
confidence: 99%